(untitled) (Manila, 2006)
Contents: Initiatives and legal instruments for international cooperation in corruption matters in Asia-Pacific; Thinking outside the box: informal and alternative measures for cooperation and mutual assistance; Overcoming legal challenges in mutual legal assistance and extradition...
Keywords: Political corruption,Tham nhũng